“Viaaado”: o imaginário do sujeito drag queen veiculado nos discursos de “super drags” - Daneluz, Vanessa Kauana (2021)
Based on the Pecheutian Discourse Analysis (1975), in this study, we intend to analyze the “Super Drags” series made available by the Netflix streaming platform. We intend to reflect on the effects of meanings produced by the series, which is the first Brazilian animation on the platform, and which suffered interdictions such as the cancellation of new seasons. With only five episodes, Super Drags addressed issues such as homosexuality, family constitution, as well as the hegemonic discourse. Thus, our objective is to analyze, through discursive sequences, the series and how an imaginary about the Drag Queen subject is conveyed in the discourses present in this series. Therefore, to achieve the presented objectives, our work will be based on Discourse Analysis theorists such as Pêcheux (1993) and Orlandi (2007); in addition to theorists who underpin the study of gender, such as Butler (2003) and Louro (2018). The clippings are separated into Discursive Sequences (SD) for better organization of the analyses. In order to understand the effects of meanings, the subject-position and the imaginary that constitutes the Drag Queen subject in Super Drags, we present a reading that makes it possible to understand how, through hegemonic discourses, Drag Queen's resistance occurs in the series under analysis. Thus, we saw that Drag art is plural and expresses the uniqueness of each subject, which goes beyond joy and extends to a confrontation position; considering that, behind all the wigs, garments, and flashy makeup, there are subjects who do not fit into the hegemonic discourses, but who – when performing on stage, in auditorium shows and, mainly, in Super Drags, being, therefore, superheroines – find their self-esteem imbued with authority which is substantial to their resistance within a society which represses them.